Taiji’s Design Philosophy by Imagining New Practice Through Three Kingdoms Character Graphic Design - Tu, ChanJuan; Wang, Yanjun (Journal of Visual Art and Design, 2025)
The present study examined the design philosophy of Taiji with the objective of developing a novel graphic design approach and substantiating its viability through a practical graphic design implementation. Application of the Taiji design philosophy was examined by using the characters from the Three Kingdoms in a graphic design practice as a case study. The objective was to assess the practicality and effectiveness of this design approach. The outcome of the research and subsequent discussion indicates that the Taiji design philosophy represents a novel framework for interdisciplinary investigation, encompassing a design methodology centered around the principles of yin and yang contrast as well as harmony and unity. The present findings hold significance in at least two distinct manners. One of the primary objectives was to illustrate how Taiji, when viewed as a philosophical concept, offers a systematic approach for the development of graphic creativity. Additionally, the yin-yang contrast and virtual-real relationship inherent in the Taiji design philosophy facilitate the transformation of two-dimensional space into a three-dimensional visual design concept for graphic designers. Undoubtedly, numerous issues regarding the underlying principles of Taiji’s design philosophy remain unresolved.